A behavioral and welfare analysis of progressive forest taxation - Erkki Koskela; Markku Ollikainen (The Research Institute of the Finnish Economy (ETLA), 2003)
We use the Hartman rotation model to study behavioral and social welfare effects of forest tax progression. The following new results are shown for harvest and timber taxes. First, a tax-revenue neutral increase in the timber tax rate, compensated by a higher tax exemption, will shorten the optimal private rotation age. A sufficient condition for this to hold for the yield and unit taxes is that the marginal valuation of amenities is non-decreasing with the age of forest stand. Second, for the socially optimal forest taxation, if society can use the neutral site productivity tax to collect tax revenue, the proportional forest tax is enough to internalize the externality caused by private harvesting. Finally, even though site productivity tax is not available, the tax structure should be designed so that tax exemption is neutral implying that the optimal corrective forest taxes remain unchanged. – rotation ; amenity services ; forest taxation ; tax progression
Keywords: Q23; H20; 330; Forststeuer; Optimale Besteuerung; Steuertarif; Theorie